Improving the B2B Professional Legal Service Customer Experience by Leveraging AI and Related Technologies - Petersen, Mecia (2019)
In conjunction with V Formation, a Nottingham-based marketing and public relations agency, the researcher aims to establish what the current customer journey for business-to-business (B2B) legal services looks like; propose a revised customer journey map for the sector and provide suggestions on how to increase client satisfaction along this journey by the use of AI and technology.